2010
DOI: 10.4028/www.scientific.net/msf.650.193
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Reversed Austenite Amount with the Tempering Temperature in a Fe-13%Cr-4%Ni-Mo Martensitic Stainless Steel

Abstract: Tempering temperature dependence of the amount of the reversed austenite in the range of 570 oC to 680 oC was investigated by means of X-ray diffraction (XRD) measurements and transmission electron microscopy (TEM) in a low carbon Fe-13%Cr-4%Ni-Mo (wt.%) martensitic stainless steel. It was found that the reversed austenite began to form at the tempered temperature slightly above the As temperature. As the tempered temperature increased, the amount of the reversed austenite changed little in the temperature ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…During high temperature tempering, reversed austenites are preferentially formed and grown up among the martensite lath and from the original austenite grain boundary 13. The volume fraction of the reversed austenite in the specimens is controlled by two factors: the transformation volume of austenite under high temperature and the stability of austenite in tempering cooling process 14, 15…”
Section: Resultsmentioning
confidence: 99%
“…During high temperature tempering, reversed austenites are preferentially formed and grown up among the martensite lath and from the original austenite grain boundary 13. The volume fraction of the reversed austenite in the specimens is controlled by two factors: the transformation volume of austenite under high temperature and the stability of austenite in tempering cooling process 14, 15…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on the thermal behavior of low-carbon 13Cr-4Ni alloy [2] and 16Cr-5Ni-(Mo) [6] showed that the amount of retained austenite increases with increasing reversion treatment temperature, exhibiting a peak typically in the range 620-640 • C. Above this range, it decreases with increasing temperatures, leading to the formation of virgin martensite upon cooling, with increasing hardness. It has been suggested that the stability of reversed austenite initially increases because of the diffusion of nickel and other gamma-stabilizing elements from the martensitic matrix towards reverted austenite islands [7][8][9]. Above a critical tempering temperature, a gradual loss of stability would occur because of several factors, among which the most important seems to be the solute redistribution for increasing volume fractions of reversed austenite [10].…”
Section: Introductionmentioning
confidence: 99%
“…The reverted austenite stable at low temperatures is called reformed austenite forming a dispersion of austenite precipitates or austenite lamellae that remains stable upon quenching at temperatures as low as − 196 °C [1]. Higher tempering temperatures result in higher reverted austenite percentages; however, if the tempering temperature is too high within the intercritical phase field, austenite stabilizers elements Ni and Mn will be diluted into a higher fraction of reverted austenite and transform back to a hard and brittle "fresh" martensite upon cooling to room temperature [7,8]. Depending on steel compositions and how heat treatments are optimized, 25% of reformed austenite stable at room temperature can be obtained when a double tempering treatment is used in 4%Ni steels, and percentage as high as 40% in 6%Ni steel can be reached even for a single stage tempering [9,10].…”
Section: Introductionmentioning
confidence: 99%